The nuclear GYF protein CD2BP2/U5–52K is required for T cell homeostasis - Bertazzon, Miriam; Hurtado-Pico, Almudena; Plaza-Sirvent, Carlos; Schuster, Marc; Preußner, Marco; Kuropka, Benno; Liu, Fan; Kirsten, Andor Zenon Amandus; Schmitt, Xiao Jakob; König, Benjamin; Álvaro-Benito, Miguel; Abualrous, Esam T.; et al. (Frontiers in Immunology, 2024)
The question whether interference with the ubiquitous splicing machinery can lead to cell-type specific perturbation of cellular function is addressed here by T cell specific ablation of the general U5 snRNP assembly factor CD2BP2/U5-52K. This protein defines the family of nuclear GYF domain containing proteins that are ubiquitously expressed in eukaryotes with essential functions ascribed to early embryogenesis and organ function. Abrogating CD2BP2/U5-52K in T cells, allows us to delineate the consequences of splicing machinery interferences for T cell development and function. Increased T cell lymphopenia and T cell death are observed upon depletion of CD2BP2/U5-52K. A substantial increase in exon skipping coincides with the observed defect in the proliferation/differentiation balance in the absence of CD2BP2/U5-52K. Prominently, skipping of exon 7 in Mdm4 is observed, coinciding with upregulation of pro-apoptotic gene expression profiles upon CD2BP2/U5-52K depletion. Furthermore, we observe enhanced sensitivity of naïve T cells compared to memory T cells to changes in CD2BP2/U5-52K levels, indicating that that depletion of this general splicing factor leads to modulation of T cell homeostasis.